2023
DOI: 10.3390/medicina59122079
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Imaging-Guided Lung Anatomic Segmentectomy: A Single-Center Preliminary Experiment

Giorgio Cannone,
Vincenzo Verzeletti,
Alberto Busetto
et al.

Abstract: Background and objectives: VATS segmentectomy has been proven to be effective in the treatment of stage I NSCLC, but its technical complexity remains one of the most challenging aspects for thoracic surgeons. Furthermore, 3D-CT reconstruction images can help in planning and performing surgical procedures. In this paper, we present our personal experience of 11 VATS anatomical resections performed after accurate pre-operative planning with 3D reconstructions. Materials and methods: A 3D virtual model of the lun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…A wide variety of 3D CT software has recently been developed worldwide, such as Synapse Vincent (Fujifilm Medical Co., Tokyo, Japan), Ziostation 2 and REVORAS (Ziosoft, Inc., Tokyo, Japan), Materialise Mimics Innovation Suite 23 (Materialise NV, Leuven, Belgium), Deepinsight platform (Neusoft Group Ltd., Shenyang, China), and IQQA-Lung (EDDA Technology, Princeton, NJ, USA) [ 11 , 12 , 28 , 43 , 44 , 45 , 46 ]. Hagiwara et al reported that 97.8% of the 316 branches of the pulmonary artery, where 3D images were constructed using Synapse Vincent, were consistent with intraoperative findings [ 11 ].…”
Section: Current Status Of 3d Ct Images In Thoracic Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…A wide variety of 3D CT software has recently been developed worldwide, such as Synapse Vincent (Fujifilm Medical Co., Tokyo, Japan), Ziostation 2 and REVORAS (Ziosoft, Inc., Tokyo, Japan), Materialise Mimics Innovation Suite 23 (Materialise NV, Leuven, Belgium), Deepinsight platform (Neusoft Group Ltd., Shenyang, China), and IQQA-Lung (EDDA Technology, Princeton, NJ, USA) [ 11 , 12 , 28 , 43 , 44 , 45 , 46 ]. Hagiwara et al reported that 97.8% of the 316 branches of the pulmonary artery, where 3D images were constructed using Synapse Vincent, were consistent with intraoperative findings [ 11 ].…”
Section: Current Status Of 3d Ct Images In Thoracic Surgerymentioning
confidence: 99%
“…Nakao et al also reported that the 3D CT images reconstructed by REVORAS were in almost complete agreement with the intraoperative findings in 18 of 20 cases [ 12 ]. Cannone et al presented their experience of 11 VATS anatomical resections performed after accurate preoperative planning with 3D reconstructions using a commercially available software, Materialise Mimics Innovation Suite 23 [ 43 ]. Moal et al also reported 3D CT reconstruction for operative planning in nine cases of RATS segmentectomy using highly specialized software (Visible Patient, Strasbourg, France) [ 44 ].…”
Section: Current Status Of 3d Ct Images In Thoracic Surgerymentioning
confidence: 99%